2013
DOI: 10.1002/jez.b.22510
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs support the monophyly of enteropneust hemichordates

Abstract: Understanding the evolutionary history of deuterostomes requires elucidating the phylogenetic interrelationships amongst the constituent taxa. Although the monophyly and interrelationships among the three principal groups-the chordates, the echinoderms, and the hemichordates-are well established, as are the internal relationships among the echinoderm and chordate taxa, the interrelationships among the principal groups of hemichordates-the harrimaniid enteropneusts, the ptychoderid enteropneusts, and the pterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…Winchell et al 2002, Cameron et al 2005, while others suggested that the Enteropneusta are a paraphyletic group with the family Harrimaniidae as a sister group to the monophyletic Pterobranchia (Halanych 1995, Cameron et al 2000, Bourlat et al 2006, Cannon et al 2009). Recently, however, Peterson et al (2013) provided MicroRNA support for a monophyly of Enteropneusta.…”
Section: Repositoriesmentioning
confidence: 99%
“…Winchell et al 2002, Cameron et al 2005, while others suggested that the Enteropneusta are a paraphyletic group with the family Harrimaniidae as a sister group to the monophyletic Pterobranchia (Halanych 1995, Cameron et al 2000, Bourlat et al 2006, Cannon et al 2009). Recently, however, Peterson et al (2013) provided MicroRNA support for a monophyly of Enteropneusta.…”
Section: Repositoriesmentioning
confidence: 99%
“…*Acoela are sometimes combined with Xenoturbella, indicating perhaps limited molecular distinction between basic bilaterians and basic deuterostomes. Compiled after (Gyoja, 2014, Osigus, et al, 2013, Peterson, et al, 2013, Schnitzler, et al, 2014, Suga, et al, 2013, Swalla and Smith, 2008)…”
Section: Figmentioning
confidence: 99%
“…This review is organized to reflect the currently accepted systematic relationships among metazoans (Fig. 1), in particular deuterostomes (Bourlat, et al, 2006, Nosenko, et al, 2013, Osigus, et al, 2013, Peterson, et al, 2013, Satoh, 2008, Swalla and Smith, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence suggests that enteropneusts have dense agglomerations of neurons associated with a neuropil, forming two cords, ventral and dorsal, that resemble a centralized nervous system [Nomaksteinsky et al, 2009]. Moreover, phylogenomic microRNA data refute their basal position in the deuterostome lineage [Peterson et al, 2013], suggesting not only the secondary loss of brain signaling centers during development [Pani et al, 2012], but also of the brain itself in hemichordates [Hirth, 2010].…”
Section: Is Convergence a Useful Explanation For The Evolution Of Bramentioning
confidence: 99%